Peran Media Massa Dalam Memoderasi Dialog Politik - Ahmad Salman Farid (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The mass media plays an important role in moderating political dialogue in society. This study aims to examine the role of the mass media in facilitating political dialogue, observe its impact on public participation, and analyze the challenges and opportunities faced by the mass media in carrying out this role. This research approach is a literature study and media content analysis. The findings of this study provide important insights into the role of the mass media as a mediator in constructive political dialogue. Based on the analysis of the literature, this research finds that the mass media has a major role in facilitating political dialogue. The mass media provide a broad platform and communication channel for the exchange of ideas, views and political information. Through balanced reporting, in-depth analysis, and presenting diverse perspectives, the mass media can help moderate political dialogue with the aim of achieving shared understanding, increasing public participation, and forming informational public opinion.